EFEKTIVITAS PENDEKATAN STM TERHADAP HASIL BELAJAR BIOLOGI SISWA MA PALAPA NUSANTARA NW SELEBUNG KELAS X TAHUN AJARAN 2013/2014 - Indra Himayatul Asri (UNIVERSITAS HAMZANWADI, 2016)
this reserch was aimed at knowing whether science and people’s technology (STM) was effective toward student’s biology learning achiement of the tenth grade of MA Palapa Nusantara NW Selebung in the academic year 2013-2014. This reserch was experimental reserch with post-test only control group desaign. The population was all students of the tenth grade MA Palapa Nusantara NW Selebung and the sample was X-A was experimen group and X-B was control group. The research instrument was 20 items of multiple choice. The data were were analyzed using homogeneity with variant test and normality test with chi-square. The hypothesis was tested through t-test where t-test was higher than t-table (5,02 1,98. Meanwhile, the result of analysis showed that the experimeth group’s mean score was 76,75 and the control group was 60,16 it meant that Ha was accepted and the implementation of saince and people’s technology was significantly effective toward students,biology learning achiievement of the tenth grade of MA Palapa Nusantara NW Selebung in academic year 2013-2014.